Pourquoi une strategie de gestion pour les elephants d’Afrique de l’ouest? - Sebogo, Lamine (Pachyderm, 1998)
Argues that elephant management at the national level is outmoded and suggests that a cooperative effort of not only neighouring states but all West African states is necessary to maintanence of any populations. Management of elephant in this region needs to be worked on cooperatively at the global level not within the individual state or as attempt to maintain specific populations in their range.